Stylohyoid complex calcification frequency in digital panoramic radiographs of a radiology center, Lima 2020-2021 - Aguilar-Palacios, Raquel (2023)
Objective: To determine the frequency of the stylohyoid complex calcification in digital panoramic radiographs of a radiological center. Methods. The type of study was qualitative, descriptive, cross-sectional and retrospective design; 400 digital panoramic radiographs between the ages of 25 and 70 were analyzed. A visual evaluation of the digital panoramic radiographs was performed to assess the type and pattern of the stylohyoid ligament calcification. Results. The 56.8% presented calcification of the stylohyoid complex in digital panoramic radiographs; according to sex in the female group it was present in 64.6%; Regarding the age group, 65.8% presented calcification in adults aged 30-59 years-old; According to the affected side, 71.4% were bilateral, according to the radiographic appearance, type I presented a higher frequency with 50.1% on the right side and 62.5% on the left side. Finally, the most frequent calcification was the completely calcified pattern, with 23.8% on the right side and 48.5% on the left side. Conclusion. The frequency of calcification of the stylohyoid complex in digital panoramic radiographs in the sample studied was high, so it is important to use panoramic radiography as a means of diagnosis to be able to detect this type of findings that, together with a clinical evaluation, allow us to make a correct diagnosis and perform an adequate treatment.